Happy Birthday Alexei ! - Vuković, Mirjana (Sarajevo Journal of Mathematics, 2024)
In addition, I would like to send my birthday greetings to Alexei Panchishkin my long-time friend from way back in 1975, when I first was on a study stay as a doctoral "stazhor" at the famous Moscow State University – Lomonosov and first met him. At that time Alexei was one of the best and brilliant students of one of the greatest and famous scientists Yuri Ivanovich Manin from the Moscow's Lomonosov University. It was during the golden age of Russian and Soviet Mathematics. I met him, for the first time, at the Manin's lectures Algebraic Questions in Differential Equations, or, in other words, Theory of Korteweg – de Vries. Among the listeners, in the large Lomonosov's amphiteather 16-10, were numerous well-known leading Lomonosov's professors: A.I. Kostrikin, L.A. Skornykov, A.V. Mikhalev, E.S. Golod, V.A. Zorich, Yu.A. Bahturin, A.Yu. Olshansky, as well as domestic and foreign visiting professors, doctoral students, and students. Alexei Panchihkin – Lomonosov’s professor became professor and professor emeritus of the Grenoble Alpes University and a well-known scientist in the amazing worlds of numbers, functions, and varieties – the field of algebraic number theory with a special reference to the arithmetic of automorphic forms and the theory of complex and $p$-adic zeta functions, as well as the founder of new mathematical directions: Arithmetic of automorphic $p$-adic $L$-functions, Algorithmic arithmetic of function fields, Solution of a problem of Coleman-Mazur, and the author of new mathematical notions named after him: Panchishkin distributions and Panchishkin condition for the existence of motivic $p$-adic $L$-functions. Dear Alexei Panchshkin, My sincere congratulations on your 70th anniversary, once more ! Best wishes of good health and many new achievements – new books and much enthusiasm in mathematics and life. Mirjana Vuković